Effect of seed inoculation with Azospirillum brasilense and nitrogen fertilization rates on maize plant yield and silage quality - Skonieski,Fernando Reimann (2017)
ABSTRACT The objective of this study was to determine the effect of Azospirillum brasilense inoculation and different nitrogen (N) rates applied as topdressing on the productivity of a maize crop and the nutritional value of maize silage. Two experiments were conducted in the 2012/2013 and 2013/2014 harvests. Treatments were distributed in a randomized block design in a factorial arrangement, which consisted of two maize hybrids (AS 1572 and Defender) coupled with nitrogen rates (0, 60, 120, 240, and 480 kg ha-1), inoculated or uninoculated with A. brasilense. Inoculated seeds were treated with the A. brasilense strains Ab-V5 and Ab-V6. Inoculation with A. brasilense showed interaction with the hybrids, agricultural years, and nitrogen rates for the maize plant yield. In the 2012/2013 agricultural year, inoculation increased the AS 1572 hybrid silage yield by 6.16% and, in the 2013/2014 harvest, A. brasilense inoculation produced an increase of 16.15% for the Defender hybrid. Nitrogen fertilization applied at 0, 60, and 120 kg ha-1 N benefited the plants inoculated with A. brasilense. The statistical equations revealed that N rates between 0 and 184 kg ha-1 in A. brasilense inoculated plants raised the plant productivity for silage when compared with the control plants. Regarding the nutritional value of the silage, inoculation with A. brasilense increased the ether extract levels and total digestible nutrients and reduced the amount of acid detergent fiber. For all this, positive results with inoculation for silage yield are dependent on nitrogen fertilization rate. Inoculation with A. brasilense can promote changes in the maize silage quality, but with obtained results it is not possible to definitely conclude upon nutritive value of maize silage.